Development and Validation of UV-Spectroscopy Based Stability Indicating Method for the Determination of Fluoxetine Hydrochloride. Issue 6 (1st November 2016) - Kumar, Amrish; Jain, Sunil Kumar
Abstract: A simple and sensitive UV-spectrophotometric method was developed and validated for the determination of hydrochloride salt of fluoxetine in bulk form. The validation of method as a stability indicating method was based on the forced degradation reactions in acidic, basic, oxidative, thermal and photolytic conditions. A linear relationship with a correlation coefficient (R2) value of 0.999 was found between the absorbance values and related concentrations in the range of 2–24 μg/ml. The detection limit and quantitation limit were found to be 0.53 μg/ml and 1.59 μg/ml, respectively. The % recoveries were found to be 99.77–99.92 with corresponding low % RSD values which indicates the high accuracy level of developed analytical method. Under stressed acidic and basic conditions, the extent of degradation was found to be 28.46±0.425% and 22.73±0.507%, respectively. Under stressed oxidative conditions, the extent of degradation was reduced to 17.84±0.276% whereas the thermal degradation was further lowered to an extent of 9.0±0.699%. In case of photolytic stressed conditions, negligible degradation (0.71±0.157%) was observed. The overall results of forced degradation studies suggest that the developed method could be successfully adopted as a stability indicating method for the estimation of fluoxetine hydrochloride.